2001
DOI: 10.1046/j.1365-2826.2001.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Salsolinol is a Putative Endogenous Neuro‐intermediate Lobe Prolactin‐Releasing Factor

Abstract: The isolation and identification of a prolactin-releasing factor (PRF) from the neuro-intermediate lobe of the pituitary gland has been pursued for over a decade. Using high-pressure liquid chromatography with electrochemical detection (HPLC-ECD) and gas chromatography/mass spectrometry (GC/MS) (R)-salsolinol (SAL) (a dopamine-related stereo-specific tetrahydroisoquinoline) was found to be present in neuro-intermediate lobe as well as median eminence extracts of male, intact-, and ovariectomized female rats. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 31 publications
1
77
0
Order By: Relevance
“…This catechol isoquinoline may be synthesized directly from DA and acetaldehyde or indirectly, forming salsolinol-1-carboxylic acid and further to salsolinol (Naoi et al 1996(Naoi et al , 2002. Although not all enzymes of an indirect pathway of salsolinol synthesis are known, this compound and its metabolites can be detected in many areas of the brain that are also rich in DA (Toth et al 2001, Naoi et al 2002. In the current study, we have shown that salsolinol is present in the IN/ME of lactating ewes.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This catechol isoquinoline may be synthesized directly from DA and acetaldehyde or indirectly, forming salsolinol-1-carboxylic acid and further to salsolinol (Naoi et al 1996(Naoi et al , 2002. Although not all enzymes of an indirect pathway of salsolinol synthesis are known, this compound and its metabolites can be detected in many areas of the brain that are also rich in DA (Toth et al 2001, Naoi et al 2002. In the current study, we have shown that salsolinol is present in the IN/ME of lactating ewes.…”
Section: Discussionmentioning
confidence: 51%
“…Our data did not show, however, a direct proof for salsolinol synthesis in these dopaminergic nuclei. So far, the presence of salsolinol in the ME has been shown in rats (Toth et al 2001). Musshoff et al (2000), studying human brain areas involved in the aetiology of alcoholism and Parkinsonism have also found salsolinol present in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a), namely at the terminal sites (ME and NIL) of the hypothalamic neuroendocrine DAerg (NEDA) neurons [25,33]. SAL can also be synthesized enzymatically by an already purified but still not sequenced enzyme, so called SAL-synthase [25,33]. As was remarked in the previous section, SAL is likely to act as an endogenous ME and NIL-derived PRF.…”
Section: Anterior Lobe (Al)mentioning
confidence: 94%
“…Lack of interference of SAL with [3H]-spiperone binding to AL homogenates [25] indicates that SAL does not act on the D2 DA receptors that are exclusively present on lactotropes. Moreover, [3H]-SAL can bind specifically to homogenate of AL obtained from lactating rats [48].…”
Section: Possible Physiological Role Of Salsolinolmentioning
confidence: 99%